Multi-configuration Dirac–Hartree–Fock (MCDHF) calculations for Ni XXV. (March 2018) - Singh, Narendra; Aggarwal, Sunny
Abstract: We present accurate 165 fine-structure energy levels related to the configurations 1s 2 2s 2, 1s 2 2p 2, 1s 2 nƖn′l′ (n = 2, n′ = 2, 3, 4, 5, Ɩ = s, p Ɩ′ = s, p, d, f, g) of Ni XXV which may be useful ion for astrophysical and fusion plasma. For the calculations of energy levels and radiative rates, we have used the multiconfiguration Dirac-Hartree-Fock (MCDHF) method employed in GRASP2K code. The calculations are carried out in the active space approximation with the inclusion of the Breit interaction, the finite nuclear size effect, and quantum electrodynamic corrections. The transition wavelengths, transition probabilities, line strengths, and absorption oscillator strengths are reported for electric dipole (E1), electric quadrupole (E2), magnetic dipole (M1), magnetic quadrupole (M2) transitions from the ground state. We have compared our calculated results with available theoretical and experimental data and good agreement is achieved. We predict new energy levels, oscillator strengths, line strengths and transition probabilities, where no other experimental or theoretical results are available. The present complete set of results should be of great help in line identification and the interpretation of spectra, as well as in the modelling and diagnostics of astrophysical and fusion plasmas. Highlights: Calculations are performed using MCDHF method. Results for 165 fine-structure energy levels for 1s 2 2s 2, 1s 2 2p 2, 1s 2 nƖn′l′ (n = 2, n′ = 2, 3, 4, 5, Ɩ = s, p Ɩ′ = s, p, d, f, g are presented. Wavelengths, transition rates and oscillator strengths for some E1, E2, M1, M2 transitions from ground state are reported.